Enhancing Teaching Quality and Sustainability in Maritime Education: A Motivational Perspective - Baihaqi Baihaqi (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research investigates the effectiveness of motivational strategies in enhancing teaching quality and promoting sustainability within maritime education institutes. Utilising qualitative methods, including interviews with lecturers and feedback from senior cadets, the study examines key motivational factors such as autonomy, competence, and relatedness in fostering student engagement and academic success. Findings highlight the transformative impact of practical simulations, mentorship programmes, and the integration of sustainability science in curriculum design. These initiatives not only enhance students' technical proficiency but also cultivate their awareness of environmental stewardship and economic sustainability in maritime operations. The research underscores the importance of continuous professional development for educators and collaborative curriculum innovation with industry partners to align educational practices with evolving industry needs. Recommendations include enhancing stakeholder engagement and promoting interdisciplinary research to bridge academia-industry gaps. Ultimately, this study contributes to advancing educational frameworks that prepare future maritime professionals to navigate complex global challenges while fostering a resilient and socially responsible maritime sector.